The Effectiveness Of Visual Illusion Of Images In Curtain Fabric Designs (Journal of the College of Basic Education, 2025)
The art of design is a scientific trend that deserves care and attention and is no less important than other fine arts. Curtain fabric designs are subject to and clearly affected by the social and economic environment and the development taking place in the technical field, which formed motives that gave the designer the ability to deduce and innovate new relationship systems resulting from his self-sensitivity to the components from which he derives the design idea in addition to the cultural level. And its own philosophy, which are the components and motives that are relied upon in fabric designs. The research problem was defined as ((What is the nature of the image and what is its effectiveness in creating optical illusion in curtain fabric designs))? The research aims to reveal the optical illusion of the image in curtain fabric designs. The research was defined as 1-Objectivity: Printed designs for curtain fabrics. 2- Spatial: Designs of imported curtain fabrics available in local markets - for the city of Baghdad of Chinese origin. 3- Temporal: Designs of curtain fabrics for specific use (living rooms) within the time period (2024-2025). As for the second chapter, the theoretical framework included three topics: First: The effectiveness of optical illusion in curtain fabric designs, Second: The role of the image in curtain fabric designs, Third: Optical illusion and formal appearance characteristics in curtain fabric designs, The third chapter dealt with the research procedures, which included the research methodology, which was a descriptive analytical methodology. Among the most important results that the research came out with are the following: The image has an important role, as it organizes all parts of the images included in the design structure and contributes to creating the general form that shows the aesthetic and functional values ​​of the design work.